2018
DOI: 10.4172/1948-5956.1000512
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Synthesized Rhenium Acetylsalicylate Compounds on Human Astrocytoma Cell Lines

Abstract: PurposeBecause of the scarcity of suitable brain cancer drugs, researchers are frantically trying to discover novel and highly potent drugs free of side effects and drug-resistance. Rhenium compounds are known to be nontoxic and exhibit no drug resistance. For that reason, we have developed a series of novel rhenium acetylsalicylato (RAC or ASP) complexes to test their cytotoxicity on brain cancer cells. Also we have attempted to explore the DNAbinding properties of these compounds because many drugs either di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…The selective cytotoxicity has also been shown for hypoxia cells [17]. [20]. For the best compound, RAC6, the cell death was nearly 70% in cancer cells and nearly 20% in normal cells.…”
Section: The Cytotoxic Effects Are Highly Selective For the Cancer Cellsmentioning
confidence: 81%
“…The selective cytotoxicity has also been shown for hypoxia cells [17]. [20]. For the best compound, RAC6, the cell death was nearly 70% in cancer cells and nearly 20% in normal cells.…”
Section: The Cytotoxic Effects Are Highly Selective For the Cancer Cellsmentioning
confidence: 81%
“…Our preliminary findings could help in solving tumor associated macrophages formation and therapeutic interventions in the future, however more research needs to be done in elucidating the core canonical pathways involved and detailed studies of cellular mechanisms in formation of TAMs and novel drugs like Rhenium ligands in preventing TAM formation and rescue. [16]…”
Section: Discussionmentioning
confidence: 99%
“…For example, pentylcarbonato Re(CO) 3 compounds induced significant cytotoxic effects at the dose of 10 M for an exposure time of 48h in HTB-12 human astrocytoma brain cancer cells but not against CRL-2005 rat astrocyte normal brain cells [78]. Re(CO) 3 acetylsalicylato complexes showed a very selective cytotoxicity on HTB-12 human astrocytoma brain cancer cell lines and glioblastoma multiforme D54 cell lines versus rat normal brain astrocyte cells [77]. Similarly, (salicylaldehyde semicarbazone)Re(CO) 3 , that was found to react with DNA guanosine by proton transfer from the phenolic OH group to N7 of guanosine, selectively induced apoptosis against MOLT-4 cells versus normal human fibroblasts [141].…”
Section: Selectivity Of Rhenium Compounds For Cancer Cell Linesmentioning
confidence: 99%
“…The recently described series of (polypyridyl)Re(CO) 3 complexes bearing axial acetylsalicylato ligand were shown by DFT calculations to display a planar configuration. The UV titration of these complexes showed that their absorbance decreased with addition of DNA without any red shift suggesting that these complexes did not follow intercalation mechanism but were more likely to bind to the minor grooves of the DNA double helix [77]. On the other hand, the structurally similar Re(CO 3 ) pentylcarbonato complexes in which each Re atom was tethered to a nearly planar polypyridyl aromatic ligand, were found to bind through an intercalation mechanism as evidenced by X-ray structure determinations and DFT calculations [78].…”
Section: Dna Effects Of Re Complexesmentioning
confidence: 99%